Low Profile and Multiband Antenna Based on Binary Encoding and Multiobjective Optimization With Artificial Intelligence - Wenbo Geng; Guolin Tong (International Journal of Antennas and Propagation)
This paper presents a low profile and multiband antenna based on binary encoding and multiobjective optimization using artificial intelligence (AI). The antenna adopts a single-arm helical structure on the top layer and two metal parasitic middle layers above the ground. The parasitic layers are composed of 10 × 10 rectangular squares, being similar as a chessboard, and they are coded as two sets of binary sequences, respectively, according to whether there is a metal sheet at the corresponding position. The multiobjective optimization to binary coding antenna with multiple effective bands, low profile, and high gains is carried out with three steps. Firstly, the discretized parameters are converted into continuous parameters, and the crude model of the antenna is optimized. Secondly, optimization algorithms under different weight assignments to the goals are applied to optimize the antenna and produce a large amount of sample data. AI is introduced to learn and train the model and then produce a large amount of sample data, and we finally get the optimal antenna structure that satisfies the multiobjective performance. The optimized prototype of the antenna is manufactured, and its impedance is well matched with the bandwidth of 1.43–2.494 GHz and 4.62–6.75 GHz. The measured maximum gain of prototype is 7.5 dBi with 10.98%λ for profile.